(untitled) (Annals of Medical Research, 2021)
Aim: Glenohumeral subluxation (GHS) is a frequent complication of post-stroke patients which can be considered as a major predisposing factor for other disorders. We aimed to assess the frequency of GHS in patients with post-stroke shoulder pain and to determine the relationships of GHS with motor recovery, pain, functional status and depression. Material and Methods: This study has a descriptive design. A total of 73 stroke patients with shoulder pain were enrolled in this study. Patients’ demographic characteristics, disease duration, Brunnstrom motor recovery levels for upper extremities, functional ambulation scales (FAS), spasticity stages, pain levels, Barthel Index (BI) and depression scores were recorded. The presence of GHS was evaluated clinically and radiologically. Considering patients with and without GHS, clinical variables were compared.Results: Of the 73 patients, 21 (28.7%) of them had GHS. The ratio of patients in Brunnstrom Category I (Brunstrom 1-3) and non-functional ambulation level were significantly higher in patients with GHS (p 0.05). Shoulder flexion, abduction, internal rotation and external rotation ROMs were found to be significantly lower in patients with GHS (p 0.05). Pain levels and BDI scores were significantly higher, BI scores were significantly lower in patients with GHS, though (p 0.05).Conclusion: GHS is a frequent problem in stroke patients which is closely related to the motor recovery and ambulation level. Patients with GHS have a more restricted shoulder ROM, higher pain and depression scores and poor level functional independence.